(untitled) (World Economics and Finance Bulletin, 2023)
In this article, the current state of the effectiveness of the production and marketing system of agricultural products, existing problems and the current state of the influence of the marketing system on the formation of prices for products and its management, the supply of consumer markets with products and the export potential are analyzed. studied